(untitled) (Nexo Revista Científica, 2021)
This article examines the medieval utensils found on the territory of the medieval towns of Volga, Bulgaria. Statistical analysis, technical and technological analysis is carried out. Based on the analysis of material materials, ethnocultural groups are linked, their interaction, and their influence on the local Bulgarian population. Volga Bulgaria is a major state transformation on the territory of medieval Eastern Europe, which included a large number of immigrants, one of which, in this case, the Ugric component, will be considered in the article.